Seroprevalence of Toxoplasmosis in Women at Alanbar Province - Ali, Ayoub Ibrahim (International Journal of Psychosocial Rehabilitation, 2020)
This study was designed to investigate the serological spread of human toxoplasmosis disease in Anbar Governorate (Iraq).One hundred thirty five blood samples were collected for detection of human toxoplasmosis by using serological tests (latex agglutination test and ELISA). The results showed that out of 135 human samples 52 and 67 sera were positive by latex agglutination test and ELISA test respectively, with an infection rates 38.5 % and 49.6% respectively, Also it showed that the highest (46.75%) human Toxoplasma infection rate was recorded by latex agglutination test in the age group 21-44 years old, while the lowest infection rate (27.6%) was recorded in the age group under 20 years old. The infection rate of Toxoplasma according to age by using ELISA showed the highest infection rate was 53.24% in the age group 21-44 years old, while the lowest infection rate (44.8%) was recorded in the age group under 20 years old. Conclusion, Latex agglutination is less specific than ELISA for toxoplasmosis in human and Most of human goats Toxoplasma infection was recorded in the age group between 21-44 years.